Biodiesel production from waste frying oil and its application to a diesel engine - Al-Hasan, Mohammad I. (Transport, 2013)
A transesterification reaction of Waste Frying Oil (WFO) with methanol in the presence of a sodium hydroxide catalyst was performed by means of two different methods: a one-step and a two-step. The effects of NaOH concentration and the molar ratio of methanol to WFO on the conversion of WFO to biodiesel were investigated and optimized for both methods. The results showed that, for one-step method, the optimal parameters for maximum biodiesel yields were found to be methanol to WFO molar ratio of 5:1, catalyst concentration of 0.7 wt% of WFO, reaction temperature of 50°C, reaction time of 1 h and stirring speed of 200 rpm, whereas the maximum biodiesel yield reached 95%. While, for the two-step method, the optimal parameters were 3.5:1 and 0.49 wt% of WFO for the first step, and 1.5:1 and 0.21wt% of WFO for the second step, whereas the maximum biodiesel yield reached 88.3% and 96.4%, respectively. Other parameters were the same as for one-step method. The two-step method enhances the yields of biodiesel by about of 2% as compared with the one-step method. In addition, the properties of WFO, the produced biodiesel and the diesel fuel were characterized by the Fatty Acid (FA) content (except diesel fuel), using Gas Chromatography (GC) analysis, and the density, viscosity, flash point, cloud point, carbon residue, and the acid value according to ASTM D6751-12 standard. While the Cetane Number (CN), lower heating value, stoichiometric Air Fuel Ratio (AFR) and iodine value were calculated based on FA composition, the results of GC analysis showed that, the FA composition of the WFO and its methyl esters was not changed with transesterification. Palmitic (C16:0), Stearic (C18:0) and Palmitoleic (C16:1) and Oleic (C18:l) acids were the most common saturated and monounsaturated FAs, respectively. Similarly, Linoleic (C18:2) and Linolenic (C18:3) were the most common polyunsaturated FAs. The physical and chemical properties results showed that the biodiesel density, viscosity and acid value were lower than of WFO and higher than diesel fuel. Also, the molecular weight, the CN, the flash point and the carbon residue of the biodiesel were higher, and the lower heating value and the stoichiometric AFR were lower than those of diesel fuel. However, all biodiesel properties met the ASTM D6751-12 or EN 14214:2008 standards. Additionally, an experimental study was conducted to evaluate the effects of produced biodiesel and its blends with diesel fuel on a diesel engine performance in comparison with diesel fuel. The results showed that, when the engine operates on pure biodiesel and on a fuel blend, the brake power and the brake specific fuel consumption were increased, while the brake thermal efficiency and the equivalence AFR were decreased. In consequence, the produced biodiesel can be used as a diesel fuel substitute from the point of view of their characteristics similarity.First Published Online: 11 Oct 2013